Tailoring MCM-41 mesoporous silica particles through modified sol-gel process for gas separation - Sang, W.Y. (American Institute of Physics Inc., 2017)
Mobil Composition of Matter-41 (MCM-41) is recognized as a potential filler to enhance permeability of mixed matrix membrane (MMM). However, the required loading for available micron-sized MCM-41 was considerably high in order to achieve desired separation performance. In this work, reduced-size MCM-41 was synthesized to minimize filler loading, improve surface modification and enhance polymer-filler compatibility during membrane fabrication. The effect of reaction condition, stirring rate and type of post-synthesis washing solution used on particle diameter of resultant MCM-41 were investigated. It was found that MCM-41 produced at room temperature condition yield particles with smaller diameter, higher specific surface area and enhanced mesopore structure. Increase of stirring rate up to 500 rpm during synthesis also reduced the particle diameter. In addition, replacing water with methanol as the post-synthesis washing solution to remove bromide ions from the precipitate was able to further reduce the particle size by inhibiting polycondensation reaction. © 2017 Author(s).